Learning in the 21st century cyber-physical age. (2nd October 2017) - Patel, Chandrakant; Lei, Yang; Liu, Lei; Vernica, Rares; Fan, Jian; Short, Brad; Liu, Jerry; Simske, Steven J.
Abstract : The learning tools necessary to prepare the next generation of students must be shaped by the socio-economic needs of the 21st century. The needs of the 21st century – from rebuilding city scale physical infrastructure to personalized healthcare – not only require learning from the wealth of global information available on the Internet, but also the building of a strong grounding in fundamentals. History has shown that the depth in fundamentals has been achieved through conventional books. Indeed, authoritative books in physical fundamentals have been penned in the 19th century and early 20th century. We present a 21st century cyber-physical learning platform that combines the best of physical books with information systems. The systemic instantiation of the platform combines modern optics and computing to view books, scan objects, and enable interactive learning – while simultaneously benefitting from the vast pool of information on the Internet. The hybrid learning platform preserves the best of the past to pave the way for the future. It also enables future research such as meta-data and descriptive tagging of the large number of images available on the web.